Pengaruh Oral Motor Excersice terhadap Kesulitan Makan Anak Prasekolah di Kota Ambon - Lameky, Vernando Yanry; Wakanno, Grace Jeny (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Difficulty Eating difficulties in preschool children are challenges that can affect the growth, development, and health of children. One of the main causative factors is oral motor disorders that inhibit the child's ability to chew and swallow food. Oral Motor Exercise (OME) has been proposed as an effective intervention to improve eating skills by stimulating and training oral muscles. This study aims to analyze the effect of OME on eating difficulties in preschool children in Ambon City. The research method used a quasi-experiment with a pre-test and post-test design with a control group involving 30 preschool children divided into intervention and control groups. The intervention group received OME training for four weeks, while the control group only received education about healthy eating patterns. The Montreal Children's Hospital Feeding Scale (MCH-FS) measured eating difficulties before and after the intervention. The results showed that the intervention group experienced significant improvements in eating skills compared to the control group. This suggests that OME effectively improves oral motor coordination and reduces eating difficulties in preschool children. These findings support the integration of OME into pediatric nursing intervention programs and the development of public health policies related to the prevention of eating disorders in children.